Extinction and the Repeatability of the End: Wells, Cuvier, Nietzsche - Žele, Marisa (Filozofski vestnik, 2022)
The paper explores the contact between the literary notion of the end of the world as depicted in H.G. Wells’s science fiction novel The Time Machine and the concept of extinction, in the sense developed by the French naturalist Georges Cuvier, who at the turn of the 19th century formulated a thesis about the structure of the world with a built-in end. The time traveller in Wells’s novel is driven into the distant future by an obsessive desire to know the fate of the world. He encounters it on the shores of an already dead sea, where he is greeted by the image of a dying world, unmoving in the dull red light of a never-setting sun. Cuvier, on the other hand, encounters the end of the world as a reader of traces of history as told by nature through its layering and piling up. Within these layers, Cuvier recognises moments of repetitive interruptions that have left behind not only whole species and genera, but also entire worlds in the great natural history. The key question, then, is the status of the end within the proposed mechanism of return and repetition.